Potential of probiotics for use as functional foods in patients with non-infectious gastric ulcer. (May 2021) - Yang, Rongrong; Zhao, Xixi; Wu, Wanqin; Shi, Junling
Abstract: Background: Non-infectious gastric ulcer is one of the most common diseases resulting from improper eating habits, alcoholism, and excessive mental stress. It is more common than infected gastric ulcer, which is caused by Helicobacter pylori . Probiotics have been widely used as functional foods to protect human health and treat diseases of the digestive system. Many studies have examined the therapeutic effects of probiotics on the gastric ulcers caused by H. pylori infection. In contrast, few studies and clinical cases are available on the application of probiotics in the therapeutic treatment of non-infectious gastric ulcer. Scope and approach: The current causes and mechanisms of non-infectious gastric ulcers were analyzed, and current drugs and potential therapeutic substances for the treatment of non-infectious gastric ulcer were evaluated. Compared with chemical medicines and other therapies, probiotics feature many advantages and have great potential to be used for the treatment of non-infectious gastric ulcer. To comprehensively assess the potential of probiotics to be used for the treatment of non-infectious gastric ulcer, we analyzed current studies relating to the pathogenesis, theoretical basis, examples, and mechanism of probiotics for treating non-infectious gastric ulcer, as well as effective delivery systems for probiotics. The goal of this review was to provide insight into the potential of probiotics to treat non-infectious gastric ulcers and the mechanisms underlying their efficacy. Key findings and conclusions: In addition to smoking, alcohol abuse and excessive mental stress, the lack of essential elements in the body, and microfloral imbalances have been shown to be major causes of non-infectious gastric ulcer. In light of the side effects and limitations of currently used drugs, probiotic therapy has proven to be the most effective treatment. A theoretical analysis and recent findings suggest that probiotics provide numerous advantages and have great potential for treating non-infectious gastric ulcer for their ability to inhibit pathogenic intestinal bacteria, promote anti-inflammatory activity, heal gastric mucosal injury, and stimulate the immune system. The molecular mechanism of probiotics in the treatment of non-infectious gastric ulcers was analyzed. TRPV1 (transient receptor potential vanilloid 1) was proposed as a possible candidate target for the therapeutic effects of probiotics on non-infectious gastric ulcer. Graphical abstract: Image 1 Highlights: Lack of essential elements and imbalance of the flora can cause gastric ulcer. Probiotics have great potential for treating non-infectious gastric ulcer. Probiotics strengthen the gastric mucosal defense barrier. TRPV1has been proposed to be a possible candidate molecule.